Handling and Restraint of Illegal Immigrants by The Office of Immigration and The Indonesian Naval Base in Bengkulu - Sarjito, Aris; Kasih Prihantoro; Rani Adriana (Advances in Social Sciences Research Journal, 2021)
ABSTRACT The area of ​​Indonesian marine waters is very large and requires effective protection and security. The Bengkulu Naval Base carries out its functions in order to improve security and control of the sea in strategic areas, especially in the national waters that are included in the zone of Bengkulu Province. Large areas of the sea are often used by foreign immigrants to enter Indonesian jurisdiction. This makes it a threat both factual and potential, so that coordination of security in the area, especially the maritime border, is needed by presenting good synergy between agencies in handling these illegal immigrants. The Immigration Office as the holder of the enforcement function for immigration matters needs to coordinate with other agencies. This study is to analyze the handling and restraint of illegal immigrants by the Bengkulu Immigration Office and Naval Base. In this study, the data collection process was carried out by using interview, observation, and documentation study methods. Data analysis begins with data collection, data condensation, data presentation and drawing conclusions. Based on the results of research with qualitative methods, it shows that; (1) in implementing synergy it is influenced by several factors, among others; facilities and infrastructure, the criteria for each agency as well as the characteristics of the partnerships formed based on the Foreigner Supervision Team Program: (2) The restraint to the implementation of this synergy are the limited budget provided, minimal facilities and infrastructure, as well as refugee conventions to date. still not ratified: and (3) the strategy of the two agencies implemented is to hold joint meetings involving vertical and horizontal elements. Keywords: Illegal immigrants, naval base, navy, restraint